Exposure and response prevention versus risperidone for the treatment of tic disorders: a randomized controlled trial - van de Griendt, Jolande M. T. M.; Cath, Danielle C.; Wertenbroek, Agnes A. A. C. M.; Verdellen, Cara W. J.; Rath, Judith J. G.; Klugkist, Irene G.; de Bruijn, Sebastiaan F. T. M.; Verbraak, Marc J. P. M. (Frontiers in Psychiatry, 2025)
IntroductionThe aim of this study was to directly compare behavior therapy (exposure & response prevention; ERP) with pharmacotherapy (risperidone) with respect to tic severity and quality of life in patients with Tourette's disorder or tic disorders.MethodA total of 30 participants were randomly assigned to either ERP (12 weekly 1-hour sessions) or risperidone (flexible dosage of 1-6 mg) with follow-up at 3 and 9 months after end of treatment. Outcome measures included tic severity as measured by the Yale Global Tic Severity Scale, quality of life and side effects. Predefined informative hypotheses were evaluated using Bayes factors (BF), a Bayesian alternative for null hypothesis testing with p-values, that provides a more reliable and powerful method in the case of small samples. A BF larger than one indicates support for the informative hypothesis and the larger the BF, the stronger the support, with a BF between 3 and 10 being considered to provide moderate evidence.ResultsBoth ERP and Risperidone were found to be effective with respect to tic severity at end of treatment (BF 5.35). At 9 months follow-up, results remained stable (BF 4.59), with an advantage of ERP over Risperidone at 3 months follow-up (BF 3.92). With respect to quality of life, an effect was found for ERP (BF 3.70 at 3 months follow up; BF 3.08 at 9 months follow-up). Dropout rates were higher in the medication condition, mainly due to significantly more side effects halfway during treatment, fading out towards end of treatment.DiscussionBehavior therapy and medication are equally viable options in the treatment of tic disorders, with a slight preference for ERP based on follow-up results on tic severity and quality of life, and side effects.Clinical trial registrationhttps://onderzoekmetmensen.nl/nl/node/23410/pdf, identifier NL-OMON23410.